MCP-1 and CCR2 gene polymorphisms in Czech patients with allergic disorders - Izakovičová Hollá, Lydie; Mrázek, František; Petřek, Martin (International journal of immunogenetics, 2009)
Several lines of evidence suggest that chemokines play an important role in asthma and allergy. We analysed polymorphisms at -2518A/G and -2076A/T of MCP-1 and V64I of CCR2 gene in healthy subjects (n = 306) and allergic patients (n = 332). Allele and genotype frequencies did not differ significantly between groups. Nevertheless, MCP-1 variants were associated with allergen sensitization. The results suggest that MCP-1, but not CCR2 gene variants, may participate in the pathogenesis of allergic phenotypes at least in the Caucasian population.
Keywords: Receptors, CCR2; financování organizované; dospělí; Genotype; Female; Adult; ženské pohlaví; alergie; Gene Frequency; lidé; genotyp; studie případů a kontrol; frekvence genu; Financing, Organized; chemokin CCL2; Hypersensitivity; Male; Case-Control Studies; Czech Republic; Chemokine CCL2; polymorfismus genetický; alely; Česká republika; receptory CCR2; Alleles; lidé středního věku; mužské pohlaví; Polymorphism, Genetic; Middle Aged; Humans